The Building Resignation Culture in Vietnam - TUAN, DR. NGUYEN MINH (The journal of contemporary issues in business and government, 2021)
In Vietnam, regulations on resignation, dismissal, and resignation are commonly used methods to replace the leadership position of officials for different reasons when the term is not over association or term of appointment. This article only focuses on the resignation of cadres because this is a new issue and very unlikely to be feasible in Vietnam in particular and countries of Eastern cultures. The author of the article will deeply analyze the causes of the weak situation in the resignation culture in Vietnam and propose solutions to ensure the feasibility of the resignation in the future. These solutions, if implemented, will be one of the best ways to screen and replace ineffective officials, fail to complete their tasks, and ensure their capacity, prestige, morality, and strength, etc. without waiting for the end of term, expiration of appointment, or the end of working age. Since then, the resignation will become a normal part of the work of the cadres and become the behavioral culture of the cadres.